The New Possibilities for Utopia Manifestation - Mikayelyan, Meri (Bulletin of Yerevan University E: Philosophy, Psychology, 2018)
The so-called virtualization process of the society is up-to-date today, and it occurs as a result of the rapid progress of information technology. The utopia of ideal wonder future continues to live in the form of a virtual utopia which represents a real-life sequel. The virtual reality is being turned into an inferior reality, but nowadays the latter has transformed many ordinary things for us, both from individual and social perspectives. The postmodern utopia has also another vast field of manifestation, that is virtual reality. The virtual reality is an interesting option for a human to escape to the imaginary world and to live by the laws of that world.